2021
DOI: 10.1177/00220345211003828
|View full text |Cite
|
Sign up to set email alerts
|

Teledentistry and mHealth for Promotion and Prevention of Oral Health: A Systematic Review and Meta-analysis

Abstract: The dental profession has experienced a dramatic acceleration in the use of communication systems and information-based technologies over recent years, originating new paradigms for the prevention and promotion of oral health. The purpose of this systematic review was to determine the effect of teledentistry-based (telematic) strategies, reported in randomized controlled trials and quasi-randomized trials, with a focus on oral health prevention and promotion–related outcomes in patients of all ages. We searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 56 publications
(107 reference statements)
2
52
0
1
Order By: Relevance
“…This shortage of doctors can be easily fulfilled by using this technology. [ [120] , [121] , [122] , [123] ] 12 Digital health monitoring Telemedicine systems with digital health monitoring capabilities, combined with artificial intelligence and machine learning, will provide more accurate diagnoses and treatment recommendations. Using video conferencing tools and machine learning technologies with the help of each patient's case will enable refining the algorithm to provide a better diagnosis for each one.…”
Section: Telemedicine In Healthcare: Significant Application Areasmentioning
confidence: 99%
“…This shortage of doctors can be easily fulfilled by using this technology. [ [120] , [121] , [122] , [123] ] 12 Digital health monitoring Telemedicine systems with digital health monitoring capabilities, combined with artificial intelligence and machine learning, will provide more accurate diagnoses and treatment recommendations. Using video conferencing tools and machine learning technologies with the help of each patient's case will enable refining the algorithm to provide a better diagnosis for each one.…”
Section: Telemedicine In Healthcare: Significant Application Areasmentioning
confidence: 99%
“…TD has been applied in different disciplines of dentistry, including but not limited to, preventive dentistry, endodontics, orthodontics, and oral medicine settings, with promising outcomes [ 2 , 4 , 5 , 6 ]. A recent systematic review and meta-analysis of 19 studies found that TD was a very effective means for oral health improvement in terms of prevention and promotion [ 7 ]. Another systematic review of 10 studies indicated that TD can successfully be implemented in the diagnosis and detection of dental caries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review of 10 studies indicated that TD can successfully be implemented in the diagnosis and detection of dental caries [ 8 ]. The key advantages of TD include cost-effectiveness, providing access to dental care in rural areas and for frail people, reducing wait times, and making referrals in an efficient way [ 5 , 6 , 7 , 8 , 9 , 10 ]. In addition, TD is an opportunity for peer education and consultation through video conferencing, facilitating better dental care for patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Teledentistry and mobile health (mHealth) are proving to be an effective tool for the promotion of oral health in various age groups [25]. mHealth components will be incorporated in the proposed study to reduce the time needed for mothers to receive health education, adhere to physical distancing in the time of COVID-19 and make use of the popularity of these tools among the younger generations.…”
Section: Oral Health Promotion Messagesmentioning
confidence: 99%